The Role of Visual Brand Identity Consistency in Enhancing Brand Recall and Consumer Preference - Fikta Novia Ayu Safitri; Agus Sriyanto (Jurnal Ar Ro'is Mandalika (Armada), 2025)
This study explores the role of visual brand identity consistency in enhancing brand recall and consumer preference. Through a qualitative literature review, this research synthesizes existing studies that examine the impact of consistent visual brand elements, such as logos, colors, typography, and design styles, on consumer perceptions and brand recognition. The review highlights the importance of visual consistency in creating a strong, memorable brand presence in a competitive marketplace. Consistent visual branding not only facilitates easier brand recognition but also strengthens emotional connections with consumers, thereby influencing their preferences and purchase decisions. The study also discusses the psychological mechanisms behind brand recall, emphasizing how familiarity and repeated exposure to consistent visual elements can lead to higher levels of brand awareness and trust. However, the research identifies challenges for brands in maintaining visual consistency across multiple platforms and touchpoints, particularly in an era of digital transformation and dynamic consumer behaviors. Additionally, the review examines the role of cultural context and market segmentation in determining the effectiveness of visual brand identity strategies. This paper provides valuable insights for marketers and brand managers seeking to optimize their visual branding strategies to enhance consumer recall and preference. By emphasizing the need for alignment between visual identity and brand values, the study contributes to the broader understanding of how visual branding affects consumer behavior in today’s competitive market.